Suppression of gene silencing: A general strategy used by diverse DNA and RNA viruses of plants - Voinnet, Olivier (The National Academy of Sciences, 1999)
In transgenic and nontransgenic plants, viruses are both initiators and targets of a defense mechanism that is similar to posttranscriptional gene silencing (PTGS). Recently, it was found that potyviruses and cucumoviruses encode pathogenicity determinants that suppress this defense mechanism. Here, we test diverse virus types for the ability to suppress PTGS. Nicotiana benthamiana exhibiting PTGS of a green fluorescent protein transgene were infected with a range of unrelated viruses and various potato virus X vectors producing viral pathogenicity factors. Upon infection, suppression of PTGS was assessed in planta through reactivation of green fluorescence and confirmed by molecular analysis. These experiments led to the identification of three suppressors of PTGS and showed that suppression of PTGS is widely used as a counter-defense strategy by DNA and RNA viruses. However, the spatial pattern and degree of suppression varied extensively between viruses. At one extreme, there are viruses that suppress in all tissues of all infected leaves, whereas others are able to suppress only in the veins of new emerging leaves. This variation existed even between closely related members of the potexvirus group. Collectively, these results suggest that virus-encoded suppressors of gene silencing have distinct modes of action, are targeted against distinct components of the host gene-silencing machinery, and that there is dynamic evolution of the host and viral components associated with the gene-silencing mechanism.